The Role of the University in the Entrepreneurship and Innovation Ecosystem (Management and Connections Journal, 2025)
The university represents a relevant actor in the context of an entrepreneurship or innovation ecosystem, and its knowledge and technology function can be expanded by actions of a technology park or innovation agency. Thus, the objective of the article is to analyze the role of a university in the construction and promotion of the entrepreneurship and innovation ecosystem. The method consisted of descriptive qualitative research with the triangulation of semi-structured interviews, observation reports and documents. The existence of a consolidated technology park and innovation agency helps the university to fulfill its construction role. Supporting fundraising projects for startups and companies represents the role of the university in promoting the ecosystem. Finally, the importance of adjustments to the connection and communication of the university with the members of the technology park and among entrepreneurs is perceived.
Keywords: University; Technology Park; Project; Innovation Ecosystem; Entrepreneurship Ecosystem